Effect of Lockdown on Neurosurgery Trauma Patients in a Tertiary Care Hospital in India - Ashutosh Roy; S. Jaiswal; A. Bajaj; Awdhesh Yadav; M. Jaiswal; B. K. Ojha; A. Chandra; C. Srivastava (Indian Journal of Neurosurgery)
Background With an increasing number of cases of COVID-19 disease, the Indian government announced a complete lockdown on March 24, 2020, and the country remained under complete lockdown in April 2020. After ramping up health infrastructure and although cases were on the rise, the lockdown was ordered to gradually lift in May 2020. Methodology It was a retrospective cross-sectional study of all patients admitted to our medical college trauma center in April 2020 and who were compared with April 2019. We studied the prevalence and outcome of road traffic accidents (RTA), assault, and fall from height (FFH) victims admitted to our trauma center. Data were collected using an Excel sheet, and statistical analysis was done using the latest available SSPS software. Results Our study groups included 124 trauma patients from April 2020 as compared with 322 trauma patients from April 2019. The intense lockdown resulted in a decrease in the number of RTA (−72%), FFH (–29%), and assault patients (–7%). There was no statistically significant change in patients' care and management at our center in terms of mortality and morbidity. No Covid-19-positive neurosurgery trauma patients were admitted in April 2020 to our center. Conclusion During the stringent lockdown period of April 2020, there was a significant decrease in the number of trauma victims, especially RTAs. The intense lockdown resulted in a significant decrease in the proportion of trauma victims under the influence of alcohol, head injuries, fractures, and dislocations along with a decrease in the number of cases of assaults and FFH as compared with the unlock period.